Functional evaluation of cyclosporine metabolism by CYP3A4 variants and potential drug interactions - Kong, Qihui; Gao, Nanyong; Wang, Yahui; Hu, Guoxin; Qian, Jianchang; Chen, Bingbing (Frontiers in Pharmacology, 2023)
The aim of this study is to investigate the effects of CYP3A4 genetic polymorphisms on the metabolism of cyclosporine (CsA) in vitro and identify drugs that interact with CsA. An enzymatic incubation system was developed to evaluate the kinetic parameters of CYP3A4 on CsA catalysis. A total of 132 drugs were screened to identify potential drug–drug interactions. Sprague–Dawley rats were used to determine the interaction between CsA and nimodipine and nisoldipine. The metabolite AM1 was measured by ultra-performance liquid chromatography–tandem mass spectrometry. The results demonstrate that 16 CYP3A4 variants (CYP3A4.7, 8, 9, 12, 13, 14, 16, 18, 19, 23, 24, 28, 31, 32, 33, and 34) have a lower metabolic capacity for CsA, ranging from 7.19% to 72.10%, than CYP3A4.1. In contrast, the relative clearance rate of CYP3A4.5 is significantly higher than that of CYP3A4.1. Moreover, CYP3A4.20 loses its catalytic ability, and five other variants have no significant difference. A total of 12 drugs, especially calcium channel blockers, were found to remarkably inhibit the metabolism of CsA with an inhibitory rate of over 80%. Nimodipine inhibits the activity of CsA in rat liver microsomes with an IC50 of 20.54 ± 0.93 μM, while nisoldipine has an IC50 of 16.16 ± 0.78 μM. In in vivo, three groups of Sprague–Dawley rats were administered CsA with or without nimodipine or nisoldipine; the AUC(0-t) and AUC(0-∞) of CsA were significantly increased in the nimodipine group but not obviously in the nisoldipine group. Mechanistically, the inhibition mode of nimodipine on cyclosporine metabolism is a mixed inhibition. Our data show that gene polymorphisms of CYP3A4 and nimodipine remarkably affect the metabolism of CsA, thus providing a reference for the precise administration of CsA.